Penerapan Modifiksi Alat Bantu Pembelajaran Bokortasko terhadap Hasil Belajar Permainan Bulutangkis Siswa Kelas VIII A di SMPN 18 Kota Jambi Tahun 2017/2018 - Bambang Bambang (Universitas Batanghari Jambi, 2019)
Lack of student involvement in participating in physical education learning which results in learning outcomes becoming less, it is necessary to do an action that can increase student participation so that the goals of learning can be achieved. The purpose of this study was to determine the improvement in learning outcomes of badminton games in class VIII A students through the application of modifications to the bokortasko learning aids in Jambi City Middle School 18 of the academic year 2017/2018. In this study, the research design used was classroom action research (CAR) by taking action through cycle I and cycle II. Cognitive learning outcomes have increased. In the first cycle the average value of the written test was 7.8 and in the second cycle the average score of the written test was 9, so the cognitive learning results from cycle I to cycle II increased by 15.4%. Affective learning outcomes also increase. The affective average value in cycle I is 7.9, and the affective average value in cycle II is 8.2. So affective learning outcomes from cycle I to cycle II have increased by 3.8%. Psychomotor learning outcomes also increased, in the first cycle the psychomotor score was 7.6 and in the second cycle was 8.1. So psychomotor learning outcomes from cycle I to cycle II increased by 6.6%.